PRINCIPLES OF ADVANCED COMPUTER-AIDED TECHNOLOGIES APPLICATION IN INFORMATIONAL SUPPORT OF TECHNOLOGICAL PREPARATION OF PRODUCTION OF NATIONAL CIVIL AIRCRAFTS - Chitak, Vitalii (Proceedings of National Aviation University (archive), 2019)
The overview and analysis of the issue of computer integrated technologies application in automated design engineering of preparation of production of national civil aircrafts have been made. Basic principles of such technologies’ application as one of the conditions of providing high-productive aircraft-building production have been proposed.